INDONESIAN WOMEN’S ULAMA AND THE RESISTANCE AGAINST PATRIARCHAL SOCIAL CONSTRUCTION - Muhammad Chabibi (PSGA LP2M IAIN Pontianak, 2022)
This paper aims to examine the position and role of Indonesian Women's Ulama in responding to the social problems of women in the patriarchal culture of UlamÄâ€™ which is dominated by male UlamÄâ€™ in Indonesia. Using Peter L.Berger and Luckmann's (1966) social construction theory, this paper seeks to explore the capacity of Indonesian Womenâ€™s Ulama in solving socio-religious problems, especially in the field of female law and social issues in Indonesia. Law-making in Indonesia cannot be separated from the patriarchal construction built by the intellectual hegemony of male UlamÄâ€™ (Islamic scholars) and the existence of social inequality between men and women in the dominance of social interpretations which results in the dominance of masculinity in the public sector. This paper uses qualitative research methods with data collection techniques in the form of observation and documentation. The conclusions of this paper are 1) the intellectual ahistorism of women socially constructed through verbalization, visualization, and adaptation in the socio-cultural scientific tradition; 2) the cultural backwardness experienced by women when men step forward in their socio-cultural intellect in the public sector such as law, education, politics and economics.